A multicenter study to evaluate pain characteristics in osteogenesis imperfecta. Issue 1 (22nd October 2022) - Rodriguez Celin, Mercedes; Kruger, Karen M.; Caudill, Angela; Murali, Chaya N.; Nagamani, Sandesh C. S.; ,; Smith, Peter A.; Harris, Gerald F.
Abstract: The objective was to describe pain characteristics and treatments used in individuals with varying severity of osteogenesis imperfecta (OI) and investigate pain‐associated variables. This work was derived from a multicenter, longitudinal, observational, natural history study of OI conducted at 12 clinical sites of the NIH Rare Diseases Clinical Research Network's Brittle Bone Disorders Consortium. Children and adults with a clinical, biochemical, or molecular diagnosis of OI were enrolled in the study. We did a cross‐sectional analysis of chronic pain prevalence, characteristics, and treatments used for pain relief and longitudinal analysis to find the predictors of chronic pain. We included 861 individuals with OI, in 41.8% chronic pain was present, with similar frequency across OI types. Back pain was the most frequent location. Nonsteroidal anti‐inflammatory drugs followed by bisphosphonates were the most common treatment used. Participants with chronic pain missed more days from school or work/year and performed worse in all mobility metrics than participants without chronic pain. The variables more significantly associated with chronic pain were age, sex, positive history of rodding surgery, scoliosis, other medical problems, assistive devices, lower standardized height, and higher body mass index. The predictors of chronic pain for all OI types were age, use of a wheelchair, and the number of fractures/year. Chronic pain is prevalent in OI across all OI types, affects mobility, and interferes with participation. Multiple covariates were associated with chronic pain.